The floodplain forest in Tabasco, Mexico, a threatened plant community - Maldonado-Sánchez, Emerson A.; Ochoa-Gaona, Susana; Ramos-Reyes, Rodimiro; Guadarrama-Olivera, María de los Ángeles; González-Valdivia, Noel; H. J. de Jong, Bernardus (Instituto de Ecología, A.C., 2016)
The structure, composition and diversity of the floodplain forest (SMPC) of Bravaisia integerrima were studied in the two largest forest stands in Tabasco, Mexico: the Ecological Reserve Yu-Balcah (YCAH) with 271 ha, and State Park La Chontalpa (PECH) with 191 ha. In each forest stand 10 plots of 1000 m2 were sampled. Tree individuals sampled were identified to species, and evaluated in three age categories, seedlings, saplings, and adults. The relationship between species richness and sampling effort was analyzed using Chao 2, ICE, Jacknife 1, Jacknife 2 and Bootstrap. The structural analysis was based on the importance value index. The diversity of species was evaluated, using the Margalef index (DMg), α de Fisher, Shannon-Wiener (H') and equity of Pielou J. The dominance indices of Berger-Parker (d) and Simpson (D) were also used. The total number of species was 76, belonging to 64 genera and 33 botanical families. The richest family was Leguminosae with 15 species. The basal area of the sites YCAH and PECH was 37.2 and 29.5 m2ha-1, respectively. Bravaisia integerrima was the most important tree species in all stands, with an Importance Index of 277. The value of the Shannon index was 2.0 in both sites. YCAH showed the best ecological condition. Six species present in the stands are considered as threatened in Mexico (NOM-059-SEMARNAT-2010). The current extent of the floodplain forest of Bravaisia in Tabasco State is 490 ha. The results suggest that the structure and composition of this forest has been affected by human activity. As a consequence, to guarantee the conservation of these remnants of SMPC in Tabasco, it is important to verify their legal situation and the application of management plans, designed to improve the productive activities of the rural communities that live around the stands. To succeed in this endeavor, it is necessary that governmental actors, academics, non-governmental organizations, and civil society work together.